PERHITUNGAN KEBUTUHAN MATERIAL PENYEMENAN DENGAN METODE BALANCE PLUG PADA PROGRAM CEMENT PLUG SUMUR X LAPANGAN Y - Hastowo Resesiyanto (INTAN Jurnal Penelitian Tambang, 2018)
Cement plug is a method to place plug to a specific depth used cement to close the well, preventing lost circulation, sidetrack at the begining of directional drilling and to provides a place for open hole test. The cement plug methods used in this research is balanced plug method. This research conducted by collecting data on Well X, in the form of well profile data covering casing and tubing dimension. Furthermore, laboratory data for cement and additives are used. Result of research showed that the total volume of cement slurry needed is equal to 29.455 bbl, the number of sack of cement for cementing the open end interval of 81.4 meters is as much 155 sack of cement, and the total volume of fluid required to push the cement slurry into cementing zone is equal 64.15 bbl.